Cytokine and eicosanoid regulation by Schistosoma mansoniduring LSE penetration - A. C. Fusco; B. Salafsky; T. Shibuya (Mediators of Inflammation)
Cercarial penetration, in low to moderate numbers, does not cause a normal skin inflammatory response; therefore, the authors sought to determine whether cercariae can down-regulate keratinocyte activation and thus the secretion of pro-inflammatory cytokines and eicosanoids. Human living skin equivalent (LSE, Organogenesis) consisting of dermal, epidermal and stratum corneum-like layers was used as the skin substrate. The surface of the LSE membrane was exposed to 100 ng IFNγ or ~850 cercariae for 18 h. Incubation media and tissue was then assayed for IL-1α, IL-6, IL-8, TNFα, 5-HETE, 12-HETE, PGF2, LTB4, and LTC4 via RIA and Western Blots. TNFα was not detected. Secreted IL-1α levels were (mean ± S.E.M. (n)): Control, 1.03 ng ± 0.15 (11); IFNγ 1.90 ng ± 0.48 (5); cercariae, 1.79 ng ± 0.22 (22). In spite of this increase, cercariae down-regulated IL-8 (cercariae 11.13 ± 1.70 ng vs. IFNγ = 16.47 ± 0.29 ng, p = 0.04) and LTB4 (cercariae = 98.86 ± 19.65 pg/0.1 ml vs. IFNγ = 193.42 ± 44.21 pg/0.1 ml p = 0.02). No changes were seen in IL-6, 12-HETE, 5-HETE, and PGE2 levels. It is concluded that cercarial penetration causes a release of IL-1α consistent with skin trauma; however, schistosomulae may regulate the production of chemotactic (neutrophils, macrophages, T-cells, etc.) and activation factors such as IL-8 and LTB4.